2005
DOI: 10.1175/jcli3560.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and Interannual Variability of North Atlantic Hurricane Tracks

Abstract: The spatial and temporal variability of North Atlantic hurricane tracks and its possible association with the annual hurricane landfall frequency along the U.S. East Coast are studied using principal component analysis (PCA) of hurricane track density function (HTDF). The results show that, in addition to the well-documented effects of the El Niño–Southern Oscillation (ENSO) and vertical wind shear (VWS), North Atlantic HTDF is strongly modulated by the dipole mode (DM) of Atlantic sea surface temperature (SST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 33 publications
2
66
0
1
Order By: Relevance
“…There is an extensive body of literature relating ENSO and North Atlantic Oscillation (NAO) oscillations with the tropical cyclone activity and tracks in the North Atlantic. As explained by Colbert and Soden (2012 ), numerous studies have found a decrease in both basin wide and landfalling storms in the Atlantic during El Niño years (Bove et al 1998;Xie et al 2005;Kossin et al 2010). Changes in tropical cyclone tracks associated with the phase of the NAO have also been identified.…”
Section: Introductionmentioning
confidence: 87%
“…There is an extensive body of literature relating ENSO and North Atlantic Oscillation (NAO) oscillations with the tropical cyclone activity and tracks in the North Atlantic. As explained by Colbert and Soden (2012 ), numerous studies have found a decrease in both basin wide and landfalling storms in the Atlantic during El Niño years (Bove et al 1998;Xie et al 2005;Kossin et al 2010). Changes in tropical cyclone tracks associated with the phase of the NAO have also been identified.…”
Section: Introductionmentioning
confidence: 87%
“…The composites are constructed similarly to those in Fig. 5, except that the track density function (Xie et al 2005) is shown to facilitate comparison and significance testing. The RWBw-associated variability of TC tracks closely resembles the variability associated with RWBFreq (not shown).…”
Section: A Correlation and Composite Analysesmentioning
confidence: 99%
“…Previous investigations of the extratropical impacts on Atlantic TC activity have mostly focused on the North Atlantic Oscillation (NAO) (Elsner 2003;Xie et al 2005;Sabbatelli and Mann 2007;Kossin et al 2010;Villarini et al 2010;Colbert and Soden 2012;Kozar et al 2012). The NAO is associated with the variability of the midlatitude jet and a meridional seesaw in sea level pressure (SLP) over the extratropical North Atlantic.…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this result is that since the mid-1960s, satellite images have helped in the identification of the origins of TCs in the central and eastern Atlantic [55,56]. However, previous research suggests that Atlantic Basin TC tracks do tend to cluster and shift over time [54,[57][58][59][60] and evidence exists for TC activity shifting more towards the eastern Atlantic overall [56,61]. The finding that the point of origin for Irene-type TCs has shifted eastward and to lower latitude over time supports this previous research.…”
Section: Characteristics Of Track Trajectoriesmentioning
confidence: 99%
“…Six additional TCs in the current study formed west of and made landfall over Florida. Of the remaining 13 TCs, nine formed east of 60 • west longitude in the main development region for the Atlantic Basin [54]. When examining year of formation, six of seven Florida landfalls occurred during 1858-1907, while five of six landfalls over The Bahamas occurred during 1960-2011.…”
Section: Characteristics Of Track Trajectoriesmentioning
confidence: 99%